Determinasi Persistensi Laba melalui Arus Kas Operasi, Volatilitas Penjualan, dan Tingkat Utang pada Perusahaan Sektor Keuangan di Bursa Efek Indonesia Periode 2020–2024 - Ricka Hidayati Chaniago; Putri Wulandari (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of operating cash flow, sales volatility, and leverage on earnings persistence in financial sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Earnings persistence is an important indicator in assessing earnings quality and financial performance stability, particularly in the context of post-pandemic economic dynamics. This research employs a quantitative approach with a causal associative design. The data used are secondary data obtained from annual financial reports published on the official website of the Indonesia Stock Exchange and respective companies. The sample consists of 46 companies selected using purposive sampling. The data are analyzed using panel data regression to examine both partial and simultaneous effects among variables. The results are expected to indicate that operating cash flow, sales volatility, and leverage significantly influence earnings persistence. This study contributes to the development of agency theory and signaling theory and provides practical implications for management, investors, and creditors in financial decision-making.